Kualitas Pelayanan Program Mobil Konseling Denpasar Ceria pada Dinas Pemberdayaan Masyarakat dan Desa Kota Denpasar - Nuryanti, Ana Dwi; Supriliyani, Ni Wayan; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2021)
The Denpasar City Government through the Denpasar City Community and Village Empowerment Service provides free counseling services to the community in a program called